2013
DOI: 10.1371/journal.pone.0065120
|View full text |Cite
|
Sign up to set email alerts
|

A Wheat WRKY Transcription Factor TaWRKY10 Confers Tolerance to Multiple Abiotic Stresses in Transgenic Tobacco

Abstract: WRKY transcription factors are reported to be involved in defense regulation, stress response and plant growth and development. However, the precise role of WRKY transcription factors in abiotic stress tolerance is not completely understood, especially in crops. In this study, we identified and cloned 10 WRKY genes from genome of wheat (Triticum aestivum L.). TaWRKY10, a gene induced by multiple stresses, was selected for further investigation. TaWRKY10 was upregulated by treatment with polyethylene glycol, Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 72 publications
7
130
0
Order By: Relevance
“…The nucleus localization after translation and the up-regulated expression pattern upon drought and exogenous ABA indicates that TaWRKY1 is possibly involved in mediating drought responses through an ABA-dependent pathway. Several lines of evidence have shown that a subset of the WRKY family genes are functional in mediating plant tolerance to drought stress, through their roles in modulating the physiological processes associated with defensiveness of drought or related osmotic stresses (Ishiguro and Nakamura 1994;Niu et al 2012;Wang et al 2013;Sun and Yu 2015;Jia et al 2015). For instance, TaWRKY2, TaWRKY19, and TaWRKY10, the WRKY family genes in wheat, function effectively in responses to a set of abiotic stresses, such as drought, high salinity, low temperature, wounding, and the external ABA application via improvement of osmolyte accumulation and cellular ROS homeostasis (Niu et al 2012;Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleus localization after translation and the up-regulated expression pattern upon drought and exogenous ABA indicates that TaWRKY1 is possibly involved in mediating drought responses through an ABA-dependent pathway. Several lines of evidence have shown that a subset of the WRKY family genes are functional in mediating plant tolerance to drought stress, through their roles in modulating the physiological processes associated with defensiveness of drought or related osmotic stresses (Ishiguro and Nakamura 1994;Niu et al 2012;Wang et al 2013;Sun and Yu 2015;Jia et al 2015). For instance, TaWRKY2, TaWRKY19, and TaWRKY10, the WRKY family genes in wheat, function effectively in responses to a set of abiotic stresses, such as drought, high salinity, low temperature, wounding, and the external ABA application via improvement of osmolyte accumulation and cellular ROS homeostasis (Niu et al 2012;Wang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Niu et al 2012;Wang et al 2013), cotton (Gossypium hirsutum) (Jia et al 2015), and soybean (Glycine max) (Liao et al 2008). In addition, numerous WRKY family genes throughout the lower plant species, such as fern (Ceratopteris richardii), moss (Physcomitrella patens), green algae (Chlamydomonas reinhardtii), diplomonads (Giardia lamblia), and amoebozoa (Dictyostelium discoideum) (Ulker and Somssich 2004;Zhang and Wang 2005), have also been characterized to date.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of the wheat genome, the genome sequencing has not yet been completed. This severely impacts the discovery of new genes, and only 40 WRKY TFs with complete CDSs have been identified, only few of which have been further analyzed [Niu et al, 2012;Wang et al, 2013]. In this study, we first deeply excavated the full-length WRKY TFs via comprehensive analysis of the A. tauschii genome, which is the D-genome progenitor of the wheat genome.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TaWRKY2 or TaWRKY19 in Arabidopsis resulted in an increased salt and drought tolerance compared with controls [Niu et al, 2012]. TaWRKY10 could also enhance the tolerance for abiotic stress by overexpression in tobacco [Wang et al, 2013]. In addition, many WRKY TFs were shown to be involved in responding to biotic and abiotic stress in other plants, such as barley, Retama raetam, Thlaspi caerulescens , and soybeans [Pnueli et al, 2002;Marè et al, 2004;Wei et al, 2008;Zhou et al, 2008].…”
mentioning
confidence: 99%
“…Germinated seeds of maize were directly sown in Sunshine MVP potting soil and then grown in a growth chamber under 16-h light/8-h dark conditions at 25±1°C. Following 2 weeks of growth, the seedlings were grown at 4 and 40°C for cold and heat treatments, respectively, for 12 and 24 h. The seedlings were submerged in 200 mM NaCl or 20 % PEG6000 solutions for salt and drought treatments, respectively, for 12 and 24 h (Qin et al 2008;Mao et al 2010;Niu et al 2012;Zhang et al 2012b;Wang et al 2013a). For the oxidative stress and hormone treatments, solutions of 30 μM MV, 100 μM MeJA and 100 μM ABA were individually sprayed on seedlings and then the plants were allowed to grow for 12 and 24 h (Zhang et al 2012b;Niu et al 2012;Mao et al 2010).…”
Section: Plant Materials Treatments and Qrt-pcr Analysismentioning
confidence: 99%